2010
DOI: 10.2166/wst.2010.352
|View full text |Cite
|
Sign up to set email alerts
|

Towards a generic rainfall-runoff model for green roofs

Abstract: A simple conceptual model for green roof hydrological processes is shown to reproduce monitored data, both during a storm event, and over a longer continuous simulation period. The model comprises a substrate moisture storage component and a transient storage component. Storage within the substrate represents the roof's overall stormwater retention capacity (or initial losses). Following a storm event the retention capacity is restored by evapotranspiration (ET). However, standard methods for quantifying ET do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 0 publications
3
59
0
2
Order By: Relevance
“…1 for event 7. Overall values of k ranged from 0.003 to 0.065; such results are similar in magnitude to other published outcomes [1,4]. The mean values of k for each year of study showed a year-on-year increase.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…1 for event 7. Overall values of k ranged from 0.003 to 0.065; such results are similar in magnitude to other published outcomes [1,4]. The mean values of k for each year of study showed a year-on-year increase.…”
Section: Resultssupporting
confidence: 86%
“…A generic conceptual hydrological green roof model was first proposed by Kasmin et al [1] and has since been developed and validated by Stovin et al [2]. This model includes both retention and detention processes to accurately indicate green roof runoff for rainfall input data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miller, 2003;Bengtsson et al, 2005;Jarrett and Berghage, 2008;Palla et al, 2010;. Furthermore, Jarrett and Berghage (2008) and Kasmin et al (2010) attention is paid to the ET rate, which is considered to by the key parameter in green roof retention performance modelling.…”
Section: [Approximate Location Of Figure 1]mentioning
confidence: 99%
“…It should be noted that the focus here is specifically on retention performance (i.e. volumetric control); detention (temporal delay) is addressed separately (see for example, Jarrett and Berghage, 2008; Kasmin et al, 2010;Yio et al, 2012;Vesuviano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%